Trace elements and mineral chemistry of silicified wood from Thailand: colours and elemental distribution. Issue 7 (2nd October 2016) - Saminpanya, S.
ABSTRACT: Thai silicified woods were examined using electron probe microanalysis, yielding chemical data that characterised the samples into two groups: low and high silica contents (82—94 wt% and 94—98 wt%). The elements analysed in order of abundance include Si > Fe > Ca > Na > Al > Ti > K > Mg > Mn > Zr. Iron plays a major role in the colour range (red, orange, yellow, brown, grey and black) of the samples. Calcium is associated with Fe in the darker colours of the wood. Pseudo-crystallochemistry has been used for the substitution of trace elements for Si 4+ in silica polymorphs. The atomic channels that run parallel to the c-axis of silica polymorphs or lattice defects, or even the charge balance for trivalent-ion substitution for Si 4+, can accommodate monovalent ions (K + and Na + ). Vacant and atomic cavities, which are charged balanced by trivalent ions [Al 3+ or Fe 3+ substituting for Si 4+ ], are commonly occupied by divalent ions (Ca 2+, Mg 2+ and Mn 2+ ). Quadrivalent ions, Ti 4+ and Zr 4+ are non-structurally incorporated but form clusters of mineral inclusions in the samples. Several other trace-element contents are also in the form of mineral/fluid inclusions hosted in the woods.